Metabolic interaction of dietary sugars and plasma lipids with a focus on mechanisms and de novo lipogenesis. - Chong, M; Fielding, B; Frayn, K (2007)
The elevation of blood lipid concentrations in response to the consumption of low-fat high-carbohydrate diets is known as carbohydrate-induced hypertriacylglycerolaemia (HPTG). An understanding of the mechanisms involved in the interaction between carbohydrates and plasma lipids may help determine whether carbohydrate-induced HPTG would increase cardiovascular risk. There is growing evidence to suggest that the sugar component of the diet may be largely responsible, rather than the total carbohydrate. In most studies designed to investigate the mechanisms of carbohydrate-induced HPTG, the amounts and types of sugars and starches used in the diets are not specified. Findings have been mixed and inconsistent. It is proposed that the elucidation of mechanisms from current studies could have been confounded by the different ways in which sugars are metabolized in the body. At present, there are few studies that have evaluated the independent effects of dietary sugars. Interest has been focused on de novo lipogenesis (DNL), as it has recently been found to be positively correlated with increases in fasting TAG levels produced on high-carbohydrate diets, indicating that DNL may contribute to carbohydrate-induced HPTG. DNL has been found to be determined by starch:sugar in a high-carbohydrate diet and affected by different types of sugars. The presence of DNL in adipose tissue is supported by emerging gene-expression studies in human subjects. In the wake of rising intakes of sugars, further research is needed to investigate the mechanisms associated with different sugars, so that appropriate therapeutic strategies can be adopted.